KONTRIBUSI TENAGA KERJA DALAM KELUARGA TERHADAP PENDAPATAN USAHA TANAMAN MELATI (Jasminum sambac) DI DESA JINGAH HABANG ULU KECAMATAN KARANG INTAN KABUPATEN BANJAR - Subhan Fitriadi; Eddy Triatmoko (Chlorophyl, 2021)
The purpose of this research is to know the revenue, the eksplicit cost, income and, contribution of labor in the family. This research was conducted in Oktober - November 2021 at village Jingah Habang Ulu, Banjar regency. The Purposive sampling methode used was by observing 23 farmers in village Jingah Habang Ulu who planted Jasminum sambac plant. The Average result of the revenue is Rp. 3.800.762/farmer, the average Eksplicit cost is Rp. 1.009.120/farmer, and Average income Rp. 1.505.248/farmer, Total contribution of labours in the family 956,03% or 45,52%/farmer. And from this result of development of farming Jasminum sambac plant. We believe that it has good prospect and revenue, of the average income, tecnicall and economically. The contribution of labors in the family can increase farmers income and it should be always optimized